Kepuasan Kerja Ditinjau dari Work Life Balance, Lingkungan Kerja, dan Disiplin pada PT. Surya Buana Wisata - Andira Shela Herawati; Siti Maryam; Istiqomah Istiqomah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Employee job satisfaction is a crucial issue in HR management because it influences work-life balance, the work environment, and discipline within the company. This study aims to determine and analyze the influence of work-life balance, the work environment, and discipline on employee job satisfaction at PT. Surya Buana Wisata. The research method used is descriptive quantitative research. The population of this study was all 40 employees of PT. Surya Buana Wisata. The entire population of 40 employees was sampled using a saturated sampling technique. The research data consisted of primary and secondary data collected through observation, documentation, questionnaires, and interviews. The data analysis techniques used were the classical assumption test, multiple linear regression analysis, hypothesis testing (t-test), and the coefficient of determination test (R2 test) with data analysis using SPSS. The results of this study indicate that work-life balance has a positive and significant effect on employee job satisfaction at PT. Surya Buana Wisata. The work environment has a positive and significant effect on employee job satisfaction at PT. Surya Buana Wisata. Discipline has a positive and significant effect on employee job satisfaction at PT. Surya Buana Wisata. The results of the multiple linear regression analysis revealed that discipline had the largest regression coefficient (0.577), indicating its most dominant contribution to increasing job satisfaction compared to other variables.